O processo educacional utilizando a realidade aumentada - OLIVEIRA, Marco Antonio Santos de (Instituto Federal do Amapá, 2021)
We live in an increasingly technological world and the transformation process takes place at an extreme speed. With technological advances, a paradigm shift in the educational process is necessary, with the development of new methods and resources to foster the teaching and learning process, the application of ICTs in education encourages students to seek knowledge and learn from new pedagogical experiences. Augmented reality, as an innovative technology, will provide the student with a differentiated field of action in the educational process, augmented reality is a technology that integrates elements of the real world with virtual information, through cameras or sensors. What enables greater interaction and new ways of performing tasks. The common example of using this feature is the Pokémon Go game. There are two major classes of AR applications: marker-based applications and location-based applications. Augmented reality is becoming a powerful tool in the classroom. AR is multidisciplinary, it can be used in any classroom activity regardless of the subject in question, including distance learning, it is up to the teacher to enrich their classes by applying this ICT in their educational process. Augmented Reality (AR) is an expanding technology, with a wide field of exploration, contributing significantly in the area of education. Innovation aims to make life easier and better. It provides students with better communication and a new way of thinking about the world.